Synthesis and Electrical Conductivity of N-(3-(Trifluoromethyl)Benzylidine)Thiosemicarbazide towards Dyes Sensitized Solar Cell - Uwaisulqarni M. Osman; Azieda Syafika N. Farizal; Nurhayati Ishak; Razali Mohd Hasmizam; M.I.N. Isa (Trans Tech Publication, 2024)
Non-Indexed Publication